2019
DOI: 10.1029/2018jg004799
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Precipitation Legacy Effects Determine the Carbon Balance of a Semiarid Grassland

Abstract: Semiarid grasslands are water-limited ecosystems where precipitation (PPT) controls the onset and duration of the growing season; however, this variable does not fully explain interannual variability of productivity at temporal scales. We examined the relationship between PPT and carbon (C) fluxes in a semiarid grassland at both seasonal and interannual scales, as well as the role of lagged effects of PPT and asymmetric sensitivities of net ecosystem carbon exchange to PPT and its components (gross ecosystem e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 56 publications
0
17
0
1
Order By: Relevance
“…On the other hand, GPP and Reco will not follow the linear relation but will converge faster towards 0 if no water is available for longer periods. For shorter periods, legacy effects must be considered [7,33,34] as they will impact these relations. A longer dataset of these similar sites with more positive and negative precipitation extremes will surely help to better understand the processes and impacts of precipitation to the carbon cycle.…”
Section: Discussion (A) Inter Annual Variabilitymentioning
confidence: 99%
“…On the other hand, GPP and Reco will not follow the linear relation but will converge faster towards 0 if no water is available for longer periods. For shorter periods, legacy effects must be considered [7,33,34] as they will impact these relations. A longer dataset of these similar sites with more positive and negative precipitation extremes will surely help to better understand the processes and impacts of precipitation to the carbon cycle.…”
Section: Discussion (A) Inter Annual Variabilitymentioning
confidence: 99%
“…Before the summer growing season, both GPP and R ec increased with increasing temperature and precipitation (Niu et al, 2011;Rey et al, 2011). However, plants are just beginning to germinate in the spring, so the carbon sequestration capacity of the ecosystem is less than the carbon release capacity (Delpierre et al, 2010;Liu et al, 2016a;Zhang et al, 2016). Therefore, the ecosystem was a net CO 2 source.…”
Section: The Seasonal and Diurnal Characteristics Of Carbon Fluxes Inmentioning
confidence: 99%
“…At SS, grasses, shrubs, cacti, and shallow rooted trees have limited access to water below the upper soil profile (Tarín et al., 2020). Note that SS and OS are documented as part of the MexFlux network but had been discontinued prior to this effort (Delgado‐Balbuena, Arredondo, et al., 2019; Vargas et al., 2013), while RM represents a new site with riparian characteristics not captured in MexFlux. Site conditions and their representativeness in the broader domain are shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…While Méndez-Barroso et al (2014) identified differences in vegetation phenology and seasonal evapotranspiration rates at two of the sites, the study was not able to distinguish sources of water nor link the plant water uptake to carbon fluxes. Thus, we deployed sensors at the subtropical scrubland and oak savanna sites that form part of the MexFlux network (Delgado-Balbuena, Arredondo, et al, 2019;Vargas et al, 2013), but which had been discontinued, and expanded observations to a third site in a riparian mesquite woodland to allow comparisons of the landscape controls described above. The new site offered the opportunity to identify how access to groundwater at a low elevation location influenced the water-energy-carbon fluxes.…”
mentioning
confidence: 99%